Welfare State, The 1945 Constitution, and Industrial Relations - Pakpahan, Muchtar (UI Scholars Hub, 2011)
Welfare state is the goal of KSBSI since its declaration on 25th April 1992. Unions which are members of the ITUC (International Trade Union Confederation) as the basic Social Democracy, their goal must either be welfare state or KSBSI. In other occasion, when Soekarno spoke before court in 1937, he stated that the goal of the proclamation the independence of Indonesia was to build a welfare state. In addition, when the founding fathers declared the 1945 Constitution, they placed welfare state as a state goal for the interest of the peoples. Without the implementation of a welfare state, the welfare of the peoples will never be realized.